(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the role and impact of artificial intelligence in modern education systems. It analyzes the main applications of AI in education, including personalized learning platforms, intelligent tutoring systems, and automated assessment tools. The study highlights the benefits of artificial intelligence, such as improved learning efficiency, increased accessibility, and reduced workload for teachers. At the same time, it discusses key challenges related to data privacy, ethical concerns, and the changing role of educators. The article emphasizes the importance of responsible and balanced integration of AI technologies to enhance educational quality and support sustainable development in education.